2017
DOI: 10.26905/jkdp.v21i1.1231
|View full text |Cite
|
Sign up to set email alerts
|

How Ready Are People for Cashless Society?

Abstract: Financial technology could be an effective tool to achieve financial inclusion. However, it needed a certain level of readiness of society. In this paper, we investigated the determinants of readiness in the implementation of digital financial services which led to cashless society. We did a survey on 993 adults in a province in Indonesia using proportional sampling technique. Estimated using ordinary least square, our empirical results showed that readiness perception had high correlation with the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…A descriptive study has been done by Wulandari et al (2016) to show customer acceptance in using e-money. Trinugroho et al (2017), on the other hand, conducted an in-depth interview to explore people readiness for a cashless society. More quantitative studies have been done by Ayudya and Wibowo (2018), Farida and Ardyan (2016) and Prayidyaningrum and Djamaludin (2016).…”
Section: Introductionmentioning
confidence: 99%
“…A descriptive study has been done by Wulandari et al (2016) to show customer acceptance in using e-money. Trinugroho et al (2017), on the other hand, conducted an in-depth interview to explore people readiness for a cashless society. More quantitative studies have been done by Ayudya and Wibowo (2018), Farida and Ardyan (2016) and Prayidyaningrum and Djamaludin (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The research considers cultural factor since its object is dominated by MSMEs, so the habit of collecting cash remains popular rather than collecting money cashless. The suburban demographic factors are found to explain differences in readiness to use digital financial services (Trinugroho et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Financial technology seems to have become a necessity for people now a day, the measurement of infrastructure forwardness needs to observe several things, one of which is the forwardness of the community to use financial technology. Research that discusses community forwardness was by (Trinugroho et al 2017), the results provide empirical evidence that perceptions of forwardness are correlated with quality of supporting infrastructure. Furthermore, (Trinugroho et al 2017)found that people who are more educated and younger are eager to adopt a financial technology system.…”
Section: Introductionmentioning
confidence: 91%